Model Manajemen Resiko pada Lembaga Keuangan Syariah - Mas'ut, Mas'ut; Mustofa, Moh. Saiful; Dianto, Alfin Yuli; Udin, Mohamad Fuad (Universitas Islam Tribakti Lirboyo Kediri, 2023)
This research analyzes the challenges and risk management models in Islamic financial institutions. This research uses the literature review method to understand the research theme in-depth. This research shows that the risk management challenges for Islamic financial institutions include the complexity of instrument types and market volatility. The risk management models in Islamic financial institutions include (i) Integrative Sharia and ERM (Enterprise Risk Management) to obtain a more holistic vision of risk throughout the organization, (ii) a Technology-Based Risk Management Model, a response for needing to incorporate technological innovation in sharia risk management practices. (iii) Specific Risk Management Model for Sharia Financial Products. There is uniqueness in Islamic financial institutions' products, so an approach tailored to each product's unique characteristics is needed, and (iv) the Sharia Microfinance Model. This model is designed to handle risks and risk management on a microfinance and inclusive financing scale.